Ankle Sprains: Clinical Practice and Guideline-Based Treatment Strategies - Pachana, Maciej; Kukuła, Piotr; Ziomek, Maciej; Piersiak, Marcin; Sawczuk, Hubert; Tomasiewicz, Anna; Zabierowski, Jan; Marschollek, Julia (Quality in Sport, 2025)
Ankle sprains, particularly lateral sprains involving the anterior talofibular ligament (ATFL), represent up to 85% of ankle injuries and are common in both athletic and general populations. Despite their prevalence, misdiagnosis and inadequate treatment can lead to chronic ankle instability and post-traumatic osteoarthritis. This narrative review synthesizes current clinical guidelines and evidence-based practices for diagnosis and treatment. Clinical assessment, supported by the Ottawa Ankle Rules, ultrasound, and MRI, enables accurate injury classification. Conservative treatment is preferred for Grade I and II injuries, with early mobilization and functional support—especially within the POLICE protocol—demonstrating superior outcomes. Exercise therapy effectively reduces recurrence, while surgical intervention is reserved for Grade III injuries or chronic instability in high-demand patients. Timely and structured rehabilitation remains key to restoring ankle function.